1986
DOI: 10.2170/jjphysiol.36.1027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tonicity on the pacemaker activity of guinea-pig sino-atrial node.

Abstract: Spontaneously beating sino-atrial node (S-A node) of guineapig was superfused with solutions of various osmolarities. The changes in the rate of spontaneous beating and in action potentials were measured. In the solution of normal tonicity, the rate of spontaneous beating was 214±6 beats/min (mean + S.E.) and the maximum rate of rise was 9.7 + 2.5 V/s. When extracellular Na " was reduced by 33%, isotonically replaced with sucrose, the heart rate was reduced to 177±8 beats/min and the maximum rate of rise was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This may suggest that the contribution of the I Cl,ir to the repolarization at positive potentials is rather small because of its inward rectification property. These data may provide new mechanistic insight into the tonicity regulation of spontaneous beating rate in guinea-pig SAN reported by Ohba in 1986 (125). In that study, it was found that decreasing the osmolarity by 30% increased the heart rate by 6% and increasing the osmolarity to 130%, 150%, and 170% decreased the heart rate to 94%, 89%, and 73%, respectively (125).…”
Section: Phenotypic Study Of Cardiac Channelssupporting
confidence: 53%
“…This may suggest that the contribution of the I Cl,ir to the repolarization at positive potentials is rather small because of its inward rectification property. These data may provide new mechanistic insight into the tonicity regulation of spontaneous beating rate in guinea-pig SAN reported by Ohba in 1986 (125). In that study, it was found that decreasing the osmolarity by 30% increased the heart rate by 6% and increasing the osmolarity to 130%, 150%, and 170% decreased the heart rate to 94%, 89%, and 73%, respectively (125).…”
Section: Phenotypic Study Of Cardiac Channelssupporting
confidence: 53%
“…This may suggest that the contribution of the I Cl,ir to the repolarization at positive potentials is rather small because of its inward rectification property. These data may provide new mechanistic insight into the tonicity regulation of spontaneous beating rate in guinea–pig SAN reported by Ohba in 1986 [49]. In that study it was found that decreasing the osmolarity by 30% increased the heart rate by 6% and increasing the osmolarity to 130, 150, and 170% decreased the heart rate to 94, 89, and 73%, respectively [49].…”
Section: Discussionmentioning
confidence: 70%
“…Our work shows that the mathematical approach provides a convenient way of understanding how individual currents contribute to SA node pacemaking. Further investigations of bifurcation structures of our model may also serve to clarify the mechanisms of abnormal SA node activities such as skipped-beat runs, annihilations, and early afterdepolarizations (11,25,39,41,48).…”
Section: Significance Of Applying Nonlinear Dynamics and Bifurcation mentioning
confidence: 98%